PERANCANGAN BOOKLET TRAYEK ANGKOT KOTA PADANG - HENKI PADLI, Drs. Syafwan, M.Si, Drs. Irwan, M.Sn (DEKAVE : Jurnal Desain Komunikasi Visual, 2014)
Apportionment of a public transportation in Padang gives facilitation for the people to get anywhere that they want. This situation has not completely complete with the spreading of media effectively, communicatively and esthetically. There is a number of public transportation which has same color and form that quite hard to differentiate with.The researcher made a design of informative media in a booklet form as the main media and other eight supporting media such as sticker, calendar, poster, neon box, x-banner, brochure, flayer and billboard. In the process of collecting the data, the researcher did some observation, interview, documentation and took data from the internet, while the booklet design and other supporting media used 5W+1H method. The goal of this final project itself is to create an informative media about public transportation in Padang which is effective, communicative and esthetic in order the users felt compatible when using it. Furthermore, it also expected to help the tourism sector for gaining the interest from its uniqueness. Booklet, sticker, calendar, poster, neon box, x-banner, brochure, flayer and billboard will become an efficient media to give information to the people as the target audience.Keyword : booklet design, route, public transportation, Padang